A Critical Review of Acid Mine Drainage Treatment - Yudha Gusti Wibowo; Rahmat Fadhilah; Hutwan Syarifuddin; Anis Tatik Maryani; Intan Andriani Putri (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2021)
Acid mine drainage has been reported to cause various environmental and human health problems. Acid mine drainage is formed due to the oxidation of sulfide minerals to water and air. This paper reports the efforts that have been made in the management and treatment of acid mine drainage. Thirty papers from reputable publishers are used as references. Efforts to prevent the formation of acid mine drainage can be made by making proper drainage and dewatering systems, making non-acid formations for rocks that have the potential to be oxidized. Active and passive treatment methods can be used to treat acid mine drainage. The active treatment method uses materials and chemicals to reduce pollutant parameters, while the passive method utilizes natural processes to reduce pollutant parameters in acid mine drainage. The combination of active and passive methods using novel materials that have been researched is recommended to produce the best system that can thoroughly remove pollutants in acid mine drainage.